2022
DOI: 10.1038/s41437-022-00554-w
|View full text |Cite
|
Sign up to set email alerts
|

Variation in mitochondrial DNA affects locomotor activity and sleep in Drosophila melanogaster

Abstract: Mitochondria are organelles that produce cellular energy in the form of ATP through oxidative phosphorylation, and this primary function is conserved among many taxa. Locomotion is a trait that is highly reliant on metabolic function and expected to be greatly affected by disruptions to mitochondrial performance. To this end, we aimed to examine how activity and sleep vary between Drosophila melanogaster strains with different geographic origins, how these patterns are affected by mitochondrial DNA (mtDNA) var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 82 publications
0
16
0
Order By: Relevance
“…Indeed, an antimycin A -treatment as well as OXPHOS cI and cV knockdown in the fat body led to a delayed development time and weakend immune response while mitovariant mtKSA2 and OXPHOS gene knockdowns in hemocytes that had no effect on the development time resulted in an enhanced innate immune response. However, when the locomotion activities and sleep patterns were studied in eight Drosophila cybrid lines, including those studied here, it was shown that especially the males that had the mitovariant mtKSA2 were moving less and sleeping more than the other cybrids [53]. This indicates that the activated immune system of the mtKSA2 flies might be energetically costly and reflect on the activity levels of the mtKSA2 cybrids.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, an antimycin A -treatment as well as OXPHOS cI and cV knockdown in the fat body led to a delayed development time and weakend immune response while mitovariant mtKSA2 and OXPHOS gene knockdowns in hemocytes that had no effect on the development time resulted in an enhanced innate immune response. However, when the locomotion activities and sleep patterns were studied in eight Drosophila cybrid lines, including those studied here, it was shown that especially the males that had the mitovariant mtKSA2 were moving less and sleeping more than the other cybrids [53]. This indicates that the activated immune system of the mtKSA2 flies might be energetically costly and reflect on the activity levels of the mtKSA2 cybrids.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, shorter sleep may represent a facet of the “fast” living strategy where sleep, as a self-maintenance process, is reduced in favour of behaviours that enhance reproductive investment. Consistent with this suggestion, individual-level differences in TST in fruit flies ( Drosophila melanogaster) are genetically determined and shorter-sleeping flies die younger (Cirelli et al 2005; Anderson et al 2022). Given that sleep loss comes at substantial costs (Rechtschaffen et al 1989; Bonnet & Arand 2003; Kushida 2004; Guyon et al 2014), we thus expect that individuals with shorter and more fragmented TST exhibit reduced immunocompetency and impaired cognitive abilities such as decision making (e.g.…”
Section: Discussionmentioning
confidence: 67%
“…The lines used herein were generated using donor mtDNA from previously described cybrid lines in a wildtype Oregon-R nuclear background [17,20]. The donor mtDNA in each of the eight lines was sampled from naturally occurring geographic variants [20].…”
Section: Generation Of Cybrid Fly Lines and Rearing Conditionsmentioning
confidence: 99%
“…Variation in the function of the mitochondria may therefore arise through mutations in nDNA or mtDNA, which can affect signalling between the mitochondrial and nuclear genomes, transcription and translation of mitochondrial proteins, and through the interaction between OXPHOS components of both the nDNA and mtDNA [16]. In the absence of infection or immune deployment, variation in mitochondrial function has been associated with decreased lifespan, changes to locomotor activity and reproductive success, as well as developmental time and weight [17][18][19][20][21]. Thus, we may predict variation in mtDNA to generate, or contribute to, heterogeneity in the immune response [16,22,23].…”
Section: Introductionmentioning
confidence: 99%